AKTIVITAS ANTIDIABETES FRAKSI ETANOL, ETIL ASETAT DAN N-HEXAN HERBA PEGAGAN (Centella asiatica L) TERHADAP MENCIT PUTIH JANTAN YANG DIINDUKSI ALOXAN - Lestari, Sovi Ayu; Hidayat, Taufik Septiyan; Suharti (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Diabetes mellitus is a chronic metabolic disorder characterized by elevated blood glucose levels resulting from impaired insulin production or function. Conventional treatments often come with side effects and high costs, prompting the exploration of herbal-based alternatives. Centella asiatica L. (commonly known as pegagan) contains various bioactive compounds with potential antidiabetic properties. This study aimed to evaluate the antidiabetic activity of ethanol, ethyl acetate, and n-hexane fractions of Centella asiatica herb in male white mice (Mus musculus) induced with alloxan, and to determine the most effective fraction in lowering blood glucose levels. The research employed a completely randomized design (CRD) in an experimental setting. Male mice were randomly assigned to five groups: negative control (1% Na-CMC), positive control (glibenclamide), and three treatment groups receiving ethanol, ethyl acetate, or n-hexane fractions of Centella asiatica at a dose of 120 mg/kg body weight. Diabetes was induced using alloxan at a dose of 100 mg/kg body weight. Blood glucose levels were measured before and after treatment at specific time intervals. The results demonstrated that all fractions of Centella asiatica exhibited blood glucose-lowering activity in diabetic mice. Among the three, the ethanol fraction produced the most significant hypoglycemic effect. Phytochemical screening revealed that the ethanol fraction contained flavonoids, triterpenoids, and saponins, which are suspected to contribute to its antidiabetic activity. In conclusion, the ethanol fraction of Centella asiatica exhibits the highest potential as an antidiabetic agent compared to the ethyl acetate and n-hexane fractions.